REGENERON PHARMACEUTICALS, INC v KYMAB LTD. Issue 8 (13th November 2018) - ,
Abstract: Patents – European patents – Pharmaceuticals – Antibody production – Genetic engineering – Transgenic mice – Infringement – Construction – Insufficiency – Biogen insufficiency – Nature of the invention – Whether a principle of general application – Enablement – Whether scope of monopoly exceeding technical contribution to the art – Appeal to Court of Appeal